Procedure for higroscopic analysis of a cold chamber envelope - Clito Afonso (2016)
The diffusion of water vapour in the atmospheric air through the elements of the envelope of a cold room, caused by the pressure gradient between the external environment and interior, is inevitable in most situations, it should be properly studied in the design phase, otherwise it can be a serious problem in the camera's use phase. In fact, if the conditions in the interior of an envelope element are such as to enable the vapour freezing of the migrant water, the increase in volume from the formation of ice causes the deformation of this element with very serious consequences, which can go up to its partial or total destruction. In this scenario, readily note the importance of vapour barriers associated with a properly designed insulation, tend to reduce not only the amount of water diffused, but also prevent the achievement of the conditions for freeze inside the engaging elements. The purpose of this work is to formulate the procedure for design of vapour barriers connected with the design of optimized thermal insulation, and then apply it to a cold chamber located in Portugal.